DISPLACEMENT ANALYSIS OF SHEET PILE WITH TIE BEAM ON BREAKWATER CONSTRUCTION BY USING PLAXIS - Maulana Arif (FROPIL (Forum Profesional Teknik Sipil), 2020)
The breakwater construction usually founded in coastal area with many public or company facilities. It is very useful to break the ocean waves so it can not reach the shore line. Furthermore, the breakwater construction is also applied as a barier for a port for ship docked. One of the type of breakwaters is tube column filled with compacted sand reinforced by sheet file and tie beam. This research will discuss about the sheet pile displacement in static and dynamic condition. Plaxis is applied as the main tool to built the 2-D model based on given data from field observation. The input parameter for this model is applied in soil stratigraphy, compacted sand column, sheet pile, tie beam, pseudostatic wave force, sea level and earthquake acceleration. The running of this model divided in three condition. There are static condition, static condition with pseudostatic wave force, and dynamic condition. The results show different displacement between the conditions. The sheet pile displacement in static condition is 3.35 cm at harbor side and 1.91 cm at open sea. The sheet pile displacement in static condition with pseudostatic wave force is 12.14 cm at harbor side and 12.08 cm at open sea. The sheet pile displacement in dynamic condition has 5 cm peak both harbor side and open sea.